Multiple moves and return migration within developing countries: A comparative analysis - Cattaneo, Andrea; Robinson, Sherman (John Wiley & Sons, 2020)
This paper sheds new light on internal migration processes by estimating stylized migration histories for populations in 31 countries. The focus is on repeat migration and on return migration back to rural areas from urban areas. Migration histories are portrayed by introducing migration pathway matrices , representing the shares of the population (by gender) that have moved or stayed in rural and urban areas over three periods (childhood and two forward periods). Using data from Demographic and Health Surveys (DHS), the estimation of national migration pathway matrices was done with an information‐theoretic procedure using maximum‐entropy econometrics to estimate migration frequencies by population groups. Moving multiple times is found to be a consolidated practice in all countries analysed. Sizeable urban‐to‐rural migration flows are found, with rural returnees often contributing substantially to these flows. This phenomenon is more pronounced in countries in relatively early phases of economic development and among male migrants. For the sample of countries in sub‐Saharan Africa, on average, 51% of men and 32% of women migrating from urban to rural areas are return migrants who lived in rural areas as children. Results indicate many migrants move multiple times: In the overall sample of countries, at least 43% of men and 36% of women who move once will move a second time (or more), accounting for nearly 120 million individuals. We find large differences in migration histories across genders, with these differences tending to be smaller for countries that are further along their economic development path and more urbanised.